A Discordant Pattern of Uptake on 68Ga-PSMA PET/CT Versus 18F-Fluciclovine PET/CT in Radiation-Induced Hepatitis: Implications for Early Postradiotherapy Imaging-Based Response Assessment. (14th April 2023) - Adediran, Omotayo A.; Lawal, Ismaheel O.; Muzahir, Saima; Bhave, Manali A.; Friend, Sarah; Fielder, Bridget; Meisel, Jane; Torres, Mylin A.; Styblo, Toncred M.; Graham, Cathy; Holbrook, Anna; Kalinsky, Kevin; et al.
Abstract: A 62-year-old woman with right-sided invasive lobular breast carcinoma completed external beam radiotherapy 6 weeks before undergoing a 68 Ga-PSMA PET/CT and 18 F-fluciclovine PET/CT scan as part of an ongoing clinical trial (NCT04750473) assessing the performance of these molecular imaging modalities in invasive lobular breast carcinoma. The 68 Ga-PSMA PET/CT demonstrated a band-like area of increased radiotracer uptake in the dome of the right lobe of the liver anteriorly, whereas 18 F-fluciclovine PET/CT done a day later revealed photopenia in the corresponding area of the liver. The external beam radiotherapy plan confirmed that the radiotherapy field overlaid the region of the hepatic discordant radiotracer uptake on the PET/CT scans.